Dimensioning of the physical area and required number of food handlers for school food services - da CUNHA, Diogo Thimoteo; Benevenuto de AMORIM, Ana Laura; Marrocos LEITE, Fernanda Helena; STEDEFELDT, Elke; de ROSSO, Veridiana Vera; BANDONI, Daniel Henrique (Revista de Nutrição, 2023)
Objective We aimed to establish equations for dimensioning of the physical area and determining the required number of food handlers in food services of schools and to compare them with reference equations. Methods It was visited 44 municipalities located in the states of São Paulo (n=36) and Rio de Janeiro (n=8) between 2013 and 2014. The physical area for school food services was evaluated using a measuring tape. For all food services, we calculated the Maximum Attendance Capacity, which is the sum of small and large meals served during the busiest shift. A validated checklist was used to evaluate food safety practices. Linear regression models were developed to establish the proposed equations. Results In total, we evaluated 205 school units. Based on the data, the following equations were established: Equation A: area of production=15.22+(maximum attendance capacity×0.02), which estimates the minimum area needed for a school food service; and Equation B: the number of food handlers=2.17+(maximum attendance capacity×0.002), to determine the minimum number of food handlers needed. These equations were established based on school food services that presented adequate food safety practices (i.e., low health risk). Conclusion It was established new equations for calculating the size of the physical area for school food services and the required number of food handlers. These new equations can be used as a starting point in management planning of a school food service.